Boylston Street, 1961 - Shwachman, Irene (Tufts Archival Research Center, 2005)
Street-level view looking northwest on right side of Boylston Street of the Boston Police Station 16 and the fire department's Ladder 15 and Engine 33 Station at the corner of Hereford Street. Police cars are parked on the street. On the right side of the photograph is a telephone booth. The Institute of Comtempory Art is currently housed in this building. 10 7/8 x 13 7/8 Photographs